OKU student, twins and siblings among 1,459 new students enrolled at UMP - Nor Salwana, Mohammad Idris (2022)
KUANTAN, 13 November 2022 - Identical twins and siblings stole the spotlight at the Universiti Malaysia Pahang (UMP) Vice-Chancellor’s Mandate Ceremony in conjunction with Student Induction Week 2022 and the New Student Pledge Reading Ceremony.